The Role of Curator in Increasing The Asset Recovery Value Through The Bankruptcy Process - Serlika Aprita; Yonani (IHSA Institute, 2022)
Bankruptcy cases in the Commercial Court since 2004 have not shown a significant increase, this is caused by the low asset recovery value which is the responsible of the curator. This condition makes debt settlement through bankruptcy unattractive for the creditors. The research question in this study was does the ratio of the curator's legal liability for errors or negligence result losses for the debtor in the legal process of managing and settling the assets of the bankrupt debtor in supporting the increase of asset recovery in bankruptcy. This research was a prescriptive normative research. The results of the study indicates that the Curator must be responsible for errors and negligences if these are the main causes of the less optimal settlement of bankruptcy documents. From a creditor's perspective, the recovery value is an indicator of the success or failure of the bankruptcy process. If asset recovery is low, creditors only feel that they have won on paper, causing them not to be interested in going through the bankruptcy process to resolve their debt problems. It is expected that the curator in carrying out his duties in managing and settling the assets of the bankrupt debtor can increase the value of the bankruptcy assets as much as possible for the benefit of the debtor and creditors. However, up to now there is still no clarity about the limits of errors and omissions. An adequate legal structure is needed to support the smooth process of bankruptcy asset settlement and legal substance related to the arrangements for the settlement and management of bankrupt debtor assets by the curator that can support the increase of asset recovery in bankruptcy. Thus, it can be seen which legal substances are obstacles so that they can hinder settlement and management of bankrupt debtor asset by the curator.